The Development of Student Religiosity in Schools in The Industrial Revolution Era 4.0 - Ahmad Rifai Ahmad Rifai (Journal of Social Science, 2020)
The era of the industrial revolution 4.0 has brought about changes in social interaction. Initially, particular communication has changed to become universal. Therefore, education readiness is needed in Indonesia to welcome it, especially in matters of religiosity. The purpose of this study is to develop students' religious attitudes in schools in the face of the industrial revolution. The object of this study is the attitude of the religiosity of high school students in Jakarta. The scope of this research is the culture of the school, the character of students, and the religious practice of high school students in Jakarta. The method used in this study is a qualitative method with literature research and field visits to several schools in Jakarta. The finding of this study is the attitude of students' religiosity in the era of the industrial revolution 4.0 has shown an encouraging thing, it just needs to be developed following the rapid information technology. The use of digital technology needs to be improved but still in the guidance and supervision of teachers in schools.